2012
DOI: 10.1038/ni.2496
|View full text |Cite
|
Sign up to set email alerts
|

The receptor PD-1 controls follicular regulatory T cells in the lymph nodes and blood

Abstract: Newly defined CD4+CXCR5+FoxP3+ T Follicular Regulatory (TFR) cells inhibit CD4+CXCR5+FoxP3− T Follicular Helper (TFH)-mediated humoral immunity. Although PD-1 is expressed by both cell types, the role of this inhibitory receptor on TFR differentiation is unknown. Here we show that PD-1/PD-L1 deficient mice have increased lymph node TFR cells, which have enhanced suppressive capacity. We also find substantial populations of TFR cells in mouse blood, and demonstrate that blood TFR cells home to lymph nodes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
568
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 412 publications
(601 citation statements)
references
References 38 publications
(62 reference statements)
27
568
4
2
Order By: Relevance
“…However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241. Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
See 4 more Smart Citations
“…However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241. Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells. Tfr cells also inhibit Tfh cell expansion, differentiation, and production of cytokines such as IL‐21 and IL‐4 239, 240, 242. Human Tfr cells (defined as CD127 −  CD25 +  CXCR5 +  CD4 + cells) have likewise been shown to reduce antibody production in in vitro Tfh:B cell co‐culture assays 243.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
See 3 more Smart Citations